THE IMPACT OF RELIGIOUS TRADITIONS ON CONSUMERS' BEHAVIOUR AND FOOD PRODUCTS' CERTIFICATION - Decebal-Ștefăniță PĂDURE; Petru ALEXE; Nicoleta STĂNCIUC; Marius Mihai MICU; Eduard Alexandru DUMITRU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Mehedinţi County is part of the South-west Oltenia region, through its area (total, agricultural and arable – 493,289, 223,344 and 187,957 ha) representing the fifth component under the total surface and third for the agricultural area and the respective arable. The existence of a fairly vast palette of cereal crops is observed: wheat and rye, barley and two row barley, oats, corn grains, sorghum and "other cereals". Within the total area of 108,461.33 ha, maize grains, wheat and rye (weights of 50.63 and 40.37%) predominating, the rest of the crops holding weights below 5%. The county obtains a total production of 429,879.67 t, to which the largest contributions have been brought, maize grains (53.73%-higher than the surface), wheat and rye (39.61%-less weight than in the case of the surface), the rest of the crops having contributions below 4%. In relation to average production, a general level of 3,963 kg/ha is found, compared to which only maize is recorded in excess.